Comparison of inpatient versus outpatient management of pediatric peritonsillar abscess outcomes. (August 2019) - Allen, D.Z.; Rawlins, K.; Onwuka, A.; Elmaraghy, C.A.
Abstract: Introduction: Peritonsillar abscess (PTA) in pediatric patients is a challenging condition to diagnose and treat, and recurrence can occur in up to 15% of patients. This condition can be managed in various settings and there may be outcome differences depending on the choice of inpatient/outpatient management. The objective of this study was to evaluate immediate and long-term outcomes, specifically recurrence, after PTA management in the inpatient versus outpatient setting as well as specific patient characteristics leading to hospital management decisions. Methods: We conducted a retrospective cohort study of all suspected cases of PTA seen at a tertiary pediatric hospital from 2008 to 2017, and 566 confirmed cases of PTA were included in this study. Demographics, PTA management, recurrence, and subsequent tonsillectomy (immediate or within 1 year of diagnosis) were ascertained from patient medical records. We compared characteristics of patients seen in the inpatient and outpatient setting using Chi-squared and Wilcoxon-Mann-Whitney tests. Results: Patients treated in the outpatient setting were more likely to be older and have a lower rate of recurrent ear infections (p < 0.0001 and p = 0.01 respectively). Additionally, no differences in gender, Down Syndrome, or autism were found. Patients who were admitted were more likely to undergo immediate tonsillectomy within a month or tonsillectomy within one year (p < 0.0001 and p = 0.02 respectively), whereas patients in the outpatient setting were more likely to receive antibiotics alone (p < 0.0001). Outpatient management was associated with no differences in recurrence rate within 30 days (p = 0.56). However, recurrence was associated with older age, a history of recurrent tonsillitis, but not a history of ear infections (p = 0.005, p < 0.0001, and p = 0.49 respectively). A history of recurrent ear infections, recurrent tonsillitis and recurrent PTAs were associated with the decision to pursue a tonsillectomy (p = 0.003, p = 0.03, and p < 0.0001 respectively). Conclusions: Patients seen in the outpatient setting are more likely to receive antibiotics alone as their initial treatment, likely a result of certain clinical characteristics and presenting features as well as uncertain diagnosis. Inpatient status was associated with a younger age and a history of ear infections while recurrence was associated with a history of recurrent tonsillitis and older age. The recurrence rates for outpatient management were not statistically different than inpatient, suggesting that triaging and treatment of patients was occurring appropriately. The association of tonsillectomies in the inpatient group within 12 months is likely due to the higher rate of preexisting tonsil issues considering that recurrent tonsillitis, ear infections and a higher rate of PTA recurrence were all statistically correlated.